Pengaruh Kualitas Sumber Daya Manusia dan Budaya Organisasi terhadap Responsivitas Pelayanan Pegawai Badan Pendapatan Daerah Provinsi Sumatera Utara - Siregar, Anggun Oktaviani; Pane, Sri Gustina; Tahir, M. (JRMB (Jurnal Riset Manajemen & Bisnis), 2022)
The aim of this research is to determine and analyze the influence of HR quality on the service responsiveness of North Sumatra Province Regional Revenue Agency employees, to determine and analyze the influence of organizational culture on the service responsiveness of North Sumatra Province Regional Revenue Agency employees, to determine and analyze the influence of HR quality and organizational culture towards service responsiveness of North Sumatra Province Regional Revenue Agency employees. The population in this study were all employees of the Regional Revenue Agency of North Sumatra Province, namely 176 employees and sampling was carried out using total sampling so that 64 respondents were used as samples. Based on the research results, it is known that there is a positive influence of the HR quality variable on the Service Responsiveness variable, thus partially there is a significant influence between the quality of human resources on employee service responsiveness, there is a positive influence of the Organizational Culture variable on the Service Responsiveness variable) thus partially there is a significant influence between Organizational Culture on employee Service Responsiveness. The quality of human resources and organizational culture influence service responsiveness. Thus, there is a positive and significant influence on the quality of human resources and organizational culture on employee service responsiveness